Low-contrast Pattern-reversal Visual Evoked Potential in Different Spatial Frequencies - Homa Hassankarimi; Ebrahim Jafarzadehpur; Alireza Mohammadi; Seyed Mohammad Reza Noori (Journal of Ophthalmic & Vision Research, 2020)
Purpose: To evaluate the pattern-reversal visual evoked potential (PRVEP) in low-contrast, spatial frequencies in time, frequency, and time-frequency domains. Methods: PRVEP was performed in 31 normal eyes, according to the International Society of Electrophysiology of Vision (ISCEV) protocol. Test stimuli had checkerboard of 5% contrast with spatial frequencies of 1, 2, and 4 cycles per degree (cpd). For each VEP waveform, the time domain (TD) analysis, Fast Fourier Transform(FFT), and discrete wavelet transform (DWT) were performed using MATLAB software. The VEP component changes as a function of spatial frequency (SF) were compared among time, frequency, and time–frequency dimensions. Results: As a consequence of increased SF, a significant attenuation of the P100 amplitude and prolongation of P100 latency were seen, while there was no significant difference in frequency components. In the wavelet domain, an increase in SF at a contrast level of 5% enhanced DWT coefficients. However, this increase had no meaningful effect on the 7P descriptor. Conclusion: At a low contrast level of 5%, SF-dependent changes in PRVEP parameters can be better identified with the TD and DWT approaches compared to the Fourier approach. However, specific visual processing may be seen with the wavelet transform.